2020
DOI: 10.1002/elps.202000106
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm formation and extracellular microvesicles—The way of foodborne pathogens toward resistance

Abstract: Biofilm formation and extracellular microvesicles-The way of foodborne pathogens toward resistance Almost all known foodborne pathogens are able to form biofilms as one of the strategies for survival under harsh living conditions, to ward off the inhibition and the disinfection during food production, transport and storage, as well as during cleaning and sanitation of corresponding facilities. Biofilms are communities where microbial cells live under constant intracellular interaction and communication. Member… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 255 publications
(467 reference statements)
0
10
0
Order By: Relevance
“…Bacterial efflux transporters are classified into five superfamilies, including ATP-binding cassette (ABC) superfamily, major facilitator superfamily (MFS), drug and metabolite transporter (DMT) superfamily containing small multidrug resistance (SMR) family, multidrug and oligosaccharidyl-lipid/polysaccharide (MOP) exporter superfamily (multidrug and toxic compound extrusion (MATE) family), and resistance-nodulation-cell division (RND) superfamily (Begić and Josić, 2020 ). These superfamilies are involved in the outer membrane permeability which can render antibiotic ineffective against bacteria.…”
Section: Mechanisms Of Bacterial Resistance To Antibioticsmentioning
confidence: 99%
“…Bacterial efflux transporters are classified into five superfamilies, including ATP-binding cassette (ABC) superfamily, major facilitator superfamily (MFS), drug and metabolite transporter (DMT) superfamily containing small multidrug resistance (SMR) family, multidrug and oligosaccharidyl-lipid/polysaccharide (MOP) exporter superfamily (multidrug and toxic compound extrusion (MATE) family), and resistance-nodulation-cell division (RND) superfamily (Begić and Josić, 2020 ). These superfamilies are involved in the outer membrane permeability which can render antibiotic ineffective against bacteria.…”
Section: Mechanisms Of Bacterial Resistance To Antibioticsmentioning
confidence: 99%
“…Bacterial membrane vesicles, which are enveloped in a lipid bilayer and carry toxins, virulence factors, nucleic acids, and metabolites, among other substances, are the subject of intense scientific investigation and represent a new approach for effective cancer treatment [ 103 , 104 ].…”
Section: Bacterial Extracellular Vesicles As Model To Fight Cancermentioning
confidence: 99%
“…Bacterial extracellular vesicles (BEVs), also known as outer membrane vesicles (OMVs), are spherical, nanometer-sized, membrane-enveloped particles released by bacteria into the extracellular environment [ 105 , 106 ]. The name OMVs comes from the fact that they were first discovered in Gram-negative bacteria, although further scientific research has shown that BEVs are released by all classes of microbes, including Gram-positive bacteria [ 103 ]. In this review, for consistency with the publications cited herein, the name OMVs is used for extracellular vesicles of Gram-negative bacteria.…”
Section: Bacterial Extracellular Vesicles As Model To Fight Cancermentioning
confidence: 99%
“…Previous studies have discovered that L. monocytogenes biofilm shows a variety of structures: mono-layers of adhered cells; flat unstructured multilayers; honeycomb structures; or clusters with EPS [16]. The components of EPS, containing proteins, extracellular polysaccharides, DNA, and teichoic acid, can provide nutrients and allow cell-to-cell communication for the bacteria [17]. Due to its strong antibiotic resistance, virulence, and persistence, biofilm has become a significant threat to food safety.…”
Section: Introductionmentioning
confidence: 99%